The Ukrainian path in the history of the creation of the International and National Soil Science Societies (1907–1928) - Kunets , V. V.; Laktionova, T. M.; Parasochka, I. F. (AgroChemistry and Soil Science, 2025)
The article examines the history of the origin of the idea of uniting the world soil science scientific community, reveals scientific and organizational approaches for the development of Pedology as an independent science. The results of the work of the first specialized scientific forums convened with the purpose of creating the International Society of Soil Science (ISSN/ISSS) and later the Ukrainian Society of Soil Scientists (USS) are analyzed. The sequence of events in the development of sectoral scientific thought was traced and the dynamics of changes in its priority areas were revealed, and the Ukrainian component was highlighted. The chronological boundaries of the study include the years 1907–1928 – starting with the first meeting of the scientific community in the former Russian Empire, at which it was decided to hold periodic congresses of soil scientists, and the First International Agrogeological Conference to the All-Ukrainian Conference of Soil Scientists (1928), which became a decisive step to the All-Ukrainian Conference of Soil Scientists (1928), which became a decisive step in the creation of a national Society of Soil Scientists in Ukraine. World Congresses and between them international and national conferences, congresses and numerous meetings allowed scientists to exchange opinions, reach scientific consensus and thereby develop and improve the methodological and theoretical foundations of Soil Science. Scientific discussions and joint field excursions, as traditional attributes of the meetings, were also a necessary addition to the research process. Thus, through joint efforts in the creative work of soil science teams of different generations and countries, the main directions of research, scientific provisions and hypotheses were crystallized. To ensure the sequence of events, the material is presented in chronological order. The activities of Ukrainian scientists G. G. Makhov, O. N. Sokolovsky, D. G. Vilensky, G. M. Vysotsky, F. I. Levchenko, V. I. Krokos, M. K. Krupsky and others in creating the Ukrainian Society of Soil Scientists and developing a system of national consolidation of knowledge about soils are revealed. Important documents for covering this topic were periodical scientific publications of the period under study. Primary importance was given to the study of published official documents of scientific and public organizations and government agencies - decrees, protocols, decisions of scientific forums and meetings. This became the basis for clarifying individual contradictory points in the description of historical events and helped to reveal the logic of their sequential series and enrich them with real thematic content. The material is supplemented with personal memories and impressions of scientists about participation in individual world-class events. An important result of the study is the specification of the process of evolution of a modern public organization – the Ukrainian Society of Soil Scientists and Agrochemists. In fact, the date of its foundation has been proven.